Inpatient Cardiac Rehabilitation of LVAD Patients—Updated Recommendations from the Working Group of the German Society for Prevention and Rehabilitation of Cardiovascular Diseases - Reiss, Nils; Schmidt, Thomas; Langheim, Eike; Bjarnason-Wehrens, Birna; Marx, Roger; Sindermann, Jürgen R.; Knoglinger, Ernst (The Thoracic and Cardiovascular Surgeon, 2019)
Cardiac rehabilitation physicians are faced to an increasing number of heart failure patients supported by left ventricular assist devices (LVAD). Many of these patients have complex medical issues and prolonged hospitalizations and therefore need special cardiac rehabilitation strategies including psychological, social, and educational support which are actually poorly implemented.Cardiac rehabilitation with clear guidance and more evidence should be considered as an essential component of the patient care plan especially regarding the increasing number of destination patients and their long-term follow-up.In this article the working group for postimplant treatment and rehabilitation of LVAD patients of the German Society for Prevention and Rehabilitation of Cardiovascular Diseases has summarized and updated the recommendations for the cardiac rehabilitation of LVAD patients considering the latest literature.
Keywords: heart failure; left ventricular assist device; rehabilitation